MARKETING STRATEGY FOR TAMAKREASI MINIGP EVENT - Mohammad Fahreza; Yuanita Indriani (IKOPIN, 2019)
Euphoria of race event in Indonesia are very big and have many opportunity to make profit. With more than one million productive young people, Bandung has the big market target to fulfill the passion and enthusiastic race lovers. And also the growth sales of the motorcycle make and supporting component to the continuity progress on its demand highly contributing for the race event.Tamakreasi is a company based in Jakarta as a company in MICE (meetings, incentives, conferencing, exhibitions) industry. Their second MiniGP event will be held in Bandung in uncommon event place because they could not find an appropriate trade center or mall like their first event in Jakarta. That is why the probability of low traffic is considering high in their second event in Bandung. Internal analysis consists of STP and Marketing Mix analysis. On STP analysis, author found out that Tamakreasi MiniGP event targeted the costumers who lived in Bandung, like to watch unique motorcycle 208 Co-Management Vol. I, No. 2, Juni 2019race event, minimum education is high school, male gender, almost all generation, and living their lives as above middle social class. On marketing mix analysis, author found out that Tamakreasi want to deliver unique race competition experience both for their visitors and for their sponsors. External analysis consist of Porter 5 force analysis. What author found on Porter 5 forces analysis is that competitiveness tension of this industry is high, because from 5 forces there are three forces that considering high which are threat of substitutes, bargaining power of suppliers, and industry rivalry. Root caused analysis addressed three problems and two sub-problems, they are limited marketing communication activities, people did not familiar with their next venue in Bandung, and race circuit is in uncommon event space. Tamakreasi use marketing communication tools that combined as their promotional mix to solve these problems.To fix these problems, Tamakreasi use marketing communication tools which consists of Advertising, Public Relation, and Social Media. Advertising channel consists of brochure, x-banner, and billboard. Public relation channel consists of radio, TV, magazine, newspaper, and community. Social media channel consists of Facebook fan page, Instagram, youtube channel, and buzzer or social media influencer. The combination between all of these marketing communication tools called promotional mix. Promotional mix used as the strategy to overcome the issue that Tamakreasi face.